Friday

April 18, 2014

April 18, 2014

Posted by **Leslie** on Wednesday, November 28, 2012 at 9:44pm.

- Math -
**Ms. Sue**, Wednesday, November 28, 2012 at 9:48pm-75= 5(3m-3)-3m

-75 = 15m - 15 - 3m

-60 = 12m

-5 = m

**Related Questions**

factoring - let f(m)=m^3 + 3m^2 + 3m + 1 notice f(-1) = 0, so m+1 is a factor. ...

algebra - Posted this question and part of the answer was incorrect. a) 4L/3 = 6...

algebra - Factor the polynomial completely 3m^2 -75 This is how I started to ...

Algebra - 3m^3 + 27m = 3m(m^2 + 9) = 3m(m + 3)(m – 3) I miss something? is this ...

Algebra - 3m^3 + 27m = 3m(m^2 + 9) = 3m(m + 3)(m – 3) its is not done? is this a...

Man My Algebra must be annoying - 3m __ for m =20 and m = 1 5 __ 3 A. 3m = 320...

Algebra - 3m^3 + 27m = 3m(m^2 + 9) = 3m(m + 3)(m – 3)

College Math II - _m^2 -1___ * _2m -2____ = (m – 1)^2 3m + 3 Actually my ...

Impossible chemistry problem - Kinetics Challenge Problem Consider the following...

Impossible chemistry problem - Kinetics Challenge Problem Consider the following...